Foundations of research methodology in the Holy Qur'an - Islam, Md. Sirajul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The Holy Qur'an emphasizes on education, research, and development. This research aims to develop a research methodology from the Holy Qur'anic viewpoint, which can be applied in all disciplines, to conduct high quality, advanced, and acceptable research. The researcher applies three methodologies: inductive, qualitative, and analytical. The researcher focuses on many aspects of research, including Qur'anic research and research methods, Qur'anic verses that describe the foundations of research, Qur'anic research goals, research methodology, and research ethics in light of the Holy Qur'an. It exposes three main approaches in the Holy Qur'an, where Allah commands, motivates, and questions humans about research in a variety of fields, topics, and issues. Allah uses seventeen styles in commanding humans, motivating them, and questioning them about research. These styles are general, objective, informative, thematic, causative, prohibitive, reminding, competitive, certainty, specification, question, answer, guidance, conditional, comparative, challenge, and prediction style. In addition, this research identifies eighteen research terminologies in the Holy Qur'ān. These terminologies are: al-qiraatu, tafakkur, an-nazr, tadabbur, al-juhd, tadhakkur, fiqh, ta'aqqul, adrak, zann, fatabaiyyanu, as-suwal, siru, latufsidu, awa lam yarau, alam tara, fastabiqu, and as-shʻur. Similarly, the research gets eight terminologies in the Holy Qur'an that talk about researchers and their prestigious position. These terms are al-rasikhu, aulu al-bab, ahl al-dhikr, al-ʻulamaʼ, qawmun yaʻqilun, qawmun yatafakkarun, qawmun ysmaʻun, and qawmun yaʻlamun. In addition, the Glorious Qur'ān classifies research scopes into three areas: the tangible and intangible entities in heavens, in the earth, and in between heavens and earth. Research goals are categorized into immediate goals and ultimate goals from the Qur'anic perspective. It derives eleven main methodological principles from the Holy Qur'an. Twelve terminologies in the Holy Qur'an motivate to be ethical researchers. Apart from that, this research derives twenty ethical factors from the Holy Qur'anic perspective, which might guide researchers to manage high quality, outstanding, advanced, and acceptable research. Finally, the status of performing rudimentary research is farḍ al-ʻayin (individual obligatory duty) while advanced research is fard al-kifaya (sufficiency duty) for high-educated skilful ethical researchers.